29 | | $\partial_t T = \partial_i n b_i \frac{\kappa_\parallel}{\lambda_\parallel+1} b_j \partial_j T^{\lambda_\parallel+1} + \partial_i n \left ( \delta_{ij} - b_i b_j \right ) \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp + 1\right )} \partial_j T^{\lambda_\parallel+1} $ |
30 | | |
31 | | or |
32 | | |
33 | | $\partial_t T = \frac{\kappa_\parallel}{\lambda_\parallel+1} \partial_i n b_i b_j \partial_j T^{\lambda_\parallel+1} + \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp + 1\right )} \partial_i n \left ( \delta_{ij} - b_i b_j \right ) \partial_j T^{\lambda_\parallel+1} $ |
| 29 | $\partial_t T = \partial_i n b_i \frac{\kappa_\parallel}{\lambda_\parallel+1} b_j \partial_j T^{\lambda_\parallel+1} + \partial_i n \left ( \delta_{ij} - b_i b_j \right ) \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp + 1\right )} \partial_j T^{\lambda_\perp+1} $ |
| 30 | |
| 31 | or |
| 32 | |
| 33 | $\partial_t T = \frac{\kappa_\parallel}{\lambda_\parallel+1} \partial_i n b_i b_j \partial_j T^{\lambda_\parallel+1} + \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp + 1\right )} \partial_i n \left ( \delta_{ij} - b_i b_j \right ) \partial_j T^{\lambda_\perp +1} $ |
| 34 | |
| 35 | Now both of these terms are of the form |
| 36 | |
| 37 | $ A \partial_i B_{ij} \partial_j T^{\lambda+1}$ |
| 38 | |
| 39 | Now to solve this implicitly, we need to replace $T$ with $T_*$ where |
| 40 | |
| 41 | $T_* = T + \phi ( T' - T ) = (1-\phi) T + \phi T'$ |
| 42 | |
| 43 | Note for Backward Euler, $\phi = 1$ and for Crank Nicholson, $\phi = 1/2$ |
| 44 | |
| 45 | $ A \partial_i B_{ij} \partial_j T_*^{\lambda+1}$ |
| 46 | |
| 47 | so we have |
| 48 | |
| 49 | $A \partial_i B_{ij} \partial_j \left ((1-\phi) T + \phi T' \right )^{\lambda+1}$ |
| 50 | |
| 51 | Now to solve this using a linear system, we need to linearize terms involving $T'$ |
| 52 | |
| 53 | So we need to Taylor expand about $T$ |
| 54 | |
| 55 | $\left ((1-\phi) T + \phi T' \right )^{\lambda+1} \approx T^{\lambda + 1} + \left ( \lambda + 1 \right ) T^{\lambda} \phi \left ( T' - T \right ) $ |
| 56 | |
| 57 | or |
| 58 | |
| 59 | $\left ((1-\phi) T + \phi T' \right )^{\lambda+1} \approx \left ( 1 - \phi \left ( \lambda + 1 \right ) \right )T^{\lambda + 1} + \phi \left ( \lambda + 1 \right ) T^{\lambda} T'$ |
| 60 | |
| 61 | Now we could also have expanded $T_*^{\lambda+1}$ and then plug in $T_*=\left ( 1 - \phi \right ) T + \phi T'$. In that case we also get |
| 62 | |
| 63 | |
| 64 | $T_*^{\lambda + 1} \approx T^{\lambda + 1} + \left ( \lambda + 1 \right ) T^{\lambda} \left ( T_{*} - T \right ) = T^{\lambda + 1} + \left ( \lambda + 1 \right ) T^{\lambda} \phi \left ( T' - T \right )$ |
| 65 | $= \left(1 - \phi \left ( \lambda + 1\right ) \right ) T^{\lambda + 1}+ \phi \left ( \lambda + 1 \right ) T^{\lambda} T' $ |
| 66 | |
| 67 | |
| 68 | So we have |
| 69 | |
| 70 | $A \partial_i B_{ij} \partial_j \left [ \left ( 1 - \phi \left ( \lambda + 1 \right ) \right )T^{\lambda + 1} + \phi \left ( \lambda + 1 \right ) T^{\lambda} T' \right ]$ |
| 71 | |
| 72 | $A \partial_i B_{ij} \left [ \left ( 1 - \phi \left ( \lambda + 1 \right ) \right ) \partial_j T^{\lambda + 1} + \phi \left ( \lambda + 1 \right ) \partial_j T^{\lambda} T' \right ]$ |
| 73 | |
| 74 | $A \partial_i B_{ij} \left [ C_\lambda \partial_j T^{\lambda + 1} + D_\lambda \partial_j T^{\lambda} T' \right ]$ |
| 75 | |
| 76 | where $ C_\lambda= \left ( 1 - \phi \left ( \lambda + 1 \right ) \right )$ and $ D_\lambda = \phi \left ( \lambda + 1 \right )$ |
| 77 | |
| 78 | Now we can expand the derivatives and get |
| 79 | |
| 80 | $A \left ( \partial_i B_{ij} \right ) \left ( C_\lambda \partial_j T^{\lambda + 1} + D_\lambda \partial_j T^{\lambda} T' \right ) + A B_{ij} \left ( C_\lambda \partial_i \partial_j T^{\lambda + 1} + D_\lambda \partial_i \partial_j T^{\lambda} T' \right ) $ |
| 81 | |
| 82 | |